The Influence of Website-Based Learning Media on Science Learning Outcomes in Elementary School Students in the Era of Society 5.0 - Rosa Ardiana Ningrum; Wahono Widodo; Elok Sudibyo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: In the era of global society 5.0, people worldwide are faced with demands to keep pace with the development of technology and knowledge by developing their